Eksistensi Undang-Undang Sebagai Produk Hukum dalam Pemenuhan Keadilan Bagi Rakyat (Analisis Putusan Mahkamah Konstitusi Nomor 50/PUU-X/2012) - Wijayanti, Winda (Jurnal Konstitusi, 2013)
Legislation in its formation is influenced by the direction of policy. Prolegnas often defeated by political interests, that determination depends on the political direction of the lawmakers that the legislation referred to as a political product. Prolegnas is part of the political establishment and management of legislation that are instrument-building program planning Act arranged in a planned, integrated, and systematic is needed to organize the national legal system. The Law 12/2011 indicates that the substantive content of the law must satisfy the principle  of  justice and the rule of law.  In addition, the preparation of legislation must meet   the elements of the rule of law, benefits, and equity in equal proportion. Thus, the Law 2/2012 that was in the National Legislation Program is a legal product that can provide justice for the people.